Magnetic ordering and charge transport in electron-doped La1-yCeyMnO3 (0.1 ≤ y ≤ 0.3) films - Prokhorov, V.G.; Kaminsky, G.G.; Flis, V.S.; Hyun, Y.H.; Park, S.Y.; Lee, Y.P.; Svetchnikov, V.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Microstructure, magnetic and transport properties of the as-deposited La1−yCeyMnO3(0.1 ≤ y ≤ 0.3) films, prepared by a pulse laser deposition, have been investigated in wide region of temperature and magnetic field. The microstructure analysis reveals that all films have a high c-oriented texture, the orthorhombic crystal lattice and the negligible quantity of CeO2 inclusions. The observed strip-domain phase with a periodic spacing of about 3c, the crystal lattice of which is the same to the basic film phase, reveals the magnetic behavior typical for the Griffiths phase. The regions of the double-period modulated phase was found at room temperature in the y = 0.1 film, which are treated as the Mn3+/Mn2+ ordering with the partial ferromagnetic → antiferromagnetic transition at TN ≤ 80 K. At the same time, the carried out investigation manifests that the magnetic and transport properties of the electron-doped La1−yCeyMnO3 films, driven by a cation doping, are similar to that for the hole-doped La/Ca manganites. Therefore, one can conclude, that does not exist of a principle difference between the mechanisms of spin-ordering and charge-transport in the hole- and the electron-doped manganites.